The Impact of the E-Government Development Index (EGDI) on the Worldwide Governance Indicator (WGI) in European Union Countries - Lisa Sophia Yuliantini; Achmad Nurmandi (Policy & Governance Review, 2023)
This study aims to analyze the impact of the e-Government Development Index (EGDI) on the Worldwide Governance Indicator (WGI) in European Union member countries. The EGDI is an index measurement that displays conditions related to the development of e-Government implementation in the member country of the United Nations, while the WGI is a series of governance indicators issued by the world bank that measures six dimensions of governance. The research method used in this research is a mixed method with collecting and analyzing data quantitatively by using Smart PLS 0.3 version, then collecting qualitative data analysis data by using qualitative methods collecting data from relevant scientific articles. The data sources for this research were obtained from the official website of the EGDI, the official website of the WGI, and literature studies of relevant scientific articles. The result of this study shows that the implementation of e-Government based on EGDI data in European Union countries has no impact on the six indicators of WGI as a whole. This is based on the results showing that the influence of the EGDI of European Union member countries on corruption control, government effectiveness, and voice of accountability is accepted, while the impact of the EGDI of European Union member countries on political stability and the absence of violence/terrorism, the quality of regulation and the rule of law is rejected. This research contributes to complement existing research by looking at the impact of implementing e-Government in European Union countries. This research is expected to be a reference in studying the implementation of e-Government in European Union countries so that it can be implemented effectively and efficiently.